Implementation of Multi-Body Dynamics Simulation for the Conveyor Chain Drive System - Chakrit Suvanjumrat (2018)
© The Authors, published by EDP Sciences, 2017. The conveyor chain drive system which included four sprockets, four flat bars (chain guides) and one conveyor chain had been assembled into commercial software, MSC.ADAMS. The conveyor chain was connected with rollers for running on the chain guides. The multi-body dynamics (MBD) simulation was implemented to study the large displacement of chain components which happened during rotations of the symmetric model of the conveyor chain drive system. The physical experiment had obtained by construction of the conveyor chain drive system regarding the MBD model. The speeds of chain drive were adjusted by a gear motor with a converter. The trajectory of conveyor chain links which respectively meshed and ran on sprockets and chain guides was recorded by a high speed camera. Furthermore, impact-contact forces by a collision of components in the conveyor chain drive system during rotation were analysis. The comparison between MBD simulation and physical experiment of the conveyor chain drive system was performed for validation of simulation models. The MBD simulation results were in good agreement with the experimental data which obtained an average error of 3.95%.